Respuesta:
Explicación paso a paso:
x + 3 = 7
x = 7 -3
x = 4
9 + x = 12
x = 12 - 9
x = 3
2x - 5 = 19
2x = 19 + 5
2x = 24
x =24 ÷ 2
x = 12
3x + 8 = 29
3x = 29 - 8
3x = 21
x = 21 ÷ 3
x = 7
21 + 5x = 86
5x = 86 - 21
5x = 65
x = 65 ÷ 5
x = 13
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
Explicación paso a paso:
x + 3 = 7
x = 7 -3
x = 4
9 + x = 12
x = 12 - 9
x = 3
2x - 5 = 19
2x = 19 + 5
2x = 24
x =24 ÷ 2
x = 12
3x + 8 = 29
3x = 29 - 8
3x = 21
x = 21 ÷ 3
x = 7
21 + 5x = 86
5x = 86 - 21
5x = 65
x = 65 ÷ 5
x = 13